Quantitative damage analysis of brick masonry under uniaxial compression and shear using acoustic emission technology. Issue 12 (18th October 2022) - Wu, Guang‐Ming; Han, Ruiqing; Li, Shengli; Guo, Pan
Abstract: Brick masonry structures will suffer different degrees of damage in their long‐term service. The common damage modes involve compression and shear damage. The acoustic emission (AE) technology, including improved b ‐value ( Ib ‐value), signal intensity analysis, and the k ‐means clustering method, was carried out during uniaxial compression and shear experiments to qualitatively and quantitatively assess the damage state of the brick masonry. Results demonstrate that the shear damage exhibits a more obvious brittle failure characteristic compared with the uniaxial compression damage. The Ib ‐value could reflect the damage evolution state of the brick masonry whether it is uniaxial or shear damage (i.e., every decrease in the Ib ‐value is a manifestation of damage expansion). The boundary of HI ‐ S r in the signal intensity analysis is proposed to differentiate the mild, moderate, and serious damage under uniaxial compressive, and the boundary is proposed to distinguish the mild and serious damage under shear. The appearance of the signal cluster with the highest ring count, energy, and duration implies the failure of the brick masonry under uniaxial compressive and shear.